A Meta‐Analysis of the Relationship between Curiosity and Creativity. (10th July 2019) - Schutte, Nicola S.; Malouff, John M.
Abstract: Curiosity, the desire to know, may be associated with creativity, which involves generating ideas that are novel and valuable. This meta‐analytic investigation consolidated the results of studies of the association between curiosity and creativity. Across 10 studies, which included 2, 692 individuals, there was a significant association between more curiosity and greater creativity (weighted effect size r  =   .41, 95% CI [.27, .54], p  =   .0001). For studies examining the association of the exploration dimension of curiosity with creativity, the weighted effect size was r  =   .48, 95% CI [.09, .74], while for studies examining the deprivation sensitivity dimension of curiosity with creativity the weighted effect size was r  =   .20, 95% CI [.10, .29]. The association of self‐report measures of curiosity with self‐reports of creativity was r  =   .52, 95% CI [.40, .62], while the association of self‐report measures of curiosity with rated creativity was r  =   .16, 95% CI [.10, .22]. These meta‐analytic results are congruent with some theoretical assumptions regarding curiosity and creativity and can be a foundation for efforts to facilitate creativity.